Nacuzzi, Lidia R., Carina Lucaioli y Florencia S. Nesis. Pueblos nómades en un estado colonial. Chaco, Pampa, Patagonia, siglo XVIII. Buenos Aires: Antropofagia, 2008. - Svriz Wucherer, Pedro Miguel Omar (Fronteras de la historia, 2018)
.